Behavior of Reinforced Lightweight Aggregate Concrete-filled Circular Steel Tube Columns Under Axial Loading. (November 2018) - AL-Eliwi, Baraa J.M.; Ekmekyapar, Talha; AL-Samaraie, Mohanad I.A.; Doğru, M. Hanifi
Abstract: The use of lightweight aggregate concrete (LWC) is the most obvious way to reduce the self-weight of concrete-filled steel tube (CFST) columns. This paper reports an investigation of the properties of reinforced lightweight aggregate concrete-filled steel tube (RLWCFST) columns subjected to axial compression. Eighteen specimens with three length-to-diameter ( L / D ) ratios (short, medium, and long) and two diameter-to-thickness ( D / t ) ratios (thin and thick) were tested. The LWC compressive strength is 30.58 MPa. The test results are given in terms of the compression loading against end shortening curves, and the failure modes of eighteen specimens are compared and discussed. In addition, the predictions of AISC360-16 and EC4 design specifications were compared to the test results to confirm the predictions of these specifications hold for RLWCFST columns. According to the experimental results, the use of the steel-bar reinforcement improves the mechanical behavior of LWC and increases the compressive strength capacity, toughness, and ductility of the composite column. The failure modes of the columns were affected by the behavior of the reinforced and unreinforced LWC and the geometric properties of the steel tube ( L / D and D / t ratios). Steel-bar reinforcement combined with thinner steel tube provided excellent performance and using larger-diameter steel-bars instead of thick steel tube can offer improvement in compression capacity and ductility for short, medium, and long columns.